Globalisation, Black Swans, and financialisation as social constructions: A Discursive Institutional Analysis of Banamex, Citibank, and Scotiabank in Argentina. Issue 1 (2nd January 2022) - Hernandez, Christian
ABSTRACT: Despite over twenty years of political resistance, globalisation endures, both as a discourse and political project. While many works have established how discourses of globalisation serve to constrain and/or guide macroeconomic policy, the dynamic nexus that exists between microeconomic decision-making processes vis-à-vis macroeconomic conditions is a less explored matter. Epistemologically, this paper offers a means of gaining analytical purchase over the logics, motivations, and thought processes of international bankers – and the financial press, which chronicle their actions. This is accomplished via a rigorous discursive-content analysis that gauges how said agents understood globalisation, the role of finance, the state, and even how market sentiment was factored into their ontological worldview. Ultimately, the goal is to establish an historical and spatiotemporally heterogeneous analysis on if, how, and what ideas of globalisation and neoliberalism influenced/rationalized the financialization of Argentine banks during the 1990s and how these evolved en route to Argentina's 2001 collapse.